Epidemiological investigation of feline chronic gingivostomatitis and its relationship with oral microbiota in Xi’an, China - Dai, Pengxiu; Yang, Mingxia; Du, Juanjuan; Wang, Keyi; Chen, Ruiqi; Feng, Xiancheng; Chen, Chen; Zhang, Xinke (Frontiers in Veterinary Science, 2024)
Feline chronic gingivostomatitis (FCGS) is an ulcerative and/or proliferative disease that typically affects the palatoglossal folds. Because of its unknown pathogenesis and long disease course, it is difficult to treat and has a high recurrence rate. Most of the bacteria in the oral microbiota exist in the mouth symbiotically and maintain a dynamic balance, and when the balance is disrupted, they may cause disease. Disturbance of the oral microbiota may play an important role in the development of FCGS. In this study, the medical records of 3109 cats in three general pet hospitals in Xi ‘an were collected. Sixty-one cats with FCGS were investigated via questionnaires, routine oral examinations and laboratory examinations. Oral microbiota samples were collected from 16 FCGS-affected cats, and microbial species were identified by 16S rDNA sequencing. The results showed that the incidence of FCGS had no significant correlation with age, sex or breed. However, the incidence of FCGS was associated with immunization, a history of homelessness and multicat rearing environments. The number of neutrophils and the serum amyloid A concentration were increased, and the percentage of cells positive for calicivirus antigen was high in all cases. All the cats had different degrees of dental calculus, and there were problems such as loss of alveolar bone or tooth resorption. Compared with those in healthy cats, the bacterial diversity and the abundance of anaerobic bacteria were significantly increased in cats with FCGS. Porphyromonas, Treponemas and Fusobacterium were abundant in the mouths of the affected cats and may be potential pathogens of FCGS. After tooth extraction, a shift could be seen in the composition of the oral microbiota in cats with FCGS. An isolated bacteria obtained from the mouths of the affected cats was homologous to P. gulae. Both the identified oral microbiota and the isolated strain of the cats with FCGS had high sensitivity to enrofloxacin and low sensitivity to metronidazole. This study provides support to current clinical criteria in diagnosing FCGS and proposes a more suitable antibiotic therapy.